1996
DOI: 10.1002/j.1460-2075.1996.tb00422.x
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive activation of NF-kappa B is essential for transformation of rat fibroblasts by the human T-cell leukemia virus type I Tax protein.

Abstract: Human T‐cell leukemia virus type I (HTLV‐I) encodes a 40 kDa trans‐acting protein, Tax, that regulates transcription of both the proviral and cellular genes, and can transform rat fibroblasts. To determine the functional importance of its trans‐acting capacities in cell transformation, we have examined two representative pathways of transcriptional activation–HTLV‐I long terminal repeat (LTR) mediated and NF‐kappa B dependent–by mutational analysis of Tax. In contrast to a previous report, mutants lacking the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
168
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(180 citation statements)
references
References 48 publications
11
168
0
1
Order By: Relevance
“…It is not yet clear whether these cells are fully immortalized or not, but it is clear that the ability in continuing cell growth has been greatly improved in these cells. By using the same type of Tax1 mutant, the essential role of the activation of the NF-kB pathway in growth promotion was also demonstrated in rat ®broblasts recently (Yamaoka et al, 1996). Interestingly, all the long-term cultures obtained by the introduction of mutant 703 were CD8+ T-cells, while most of those obtained by the introduction of wild-type Tax1 were CD4+ T-cells.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…It is not yet clear whether these cells are fully immortalized or not, but it is clear that the ability in continuing cell growth has been greatly improved in these cells. By using the same type of Tax1 mutant, the essential role of the activation of the NF-kB pathway in growth promotion was also demonstrated in rat ®broblasts recently (Yamaoka et al, 1996). Interestingly, all the long-term cultures obtained by the introduction of mutant 703 were CD8+ T-cells, while most of those obtained by the introduction of wild-type Tax1 were CD4+ T-cells.…”
Section: Discussionmentioning
confidence: 84%
“…Through these transcriptional pathways, Tax1 activates the expression of a wide variety of cellular genes, and this is thought to mediate T-cell transformation by HTLV-I. The role of each Tax1-inducible transcriptional pathway in cell transformation has been studied in rodent ®broblasts (Smith and Greene, 1991;Yamaoka et al, 1996), however it remains completely unknown in T-cells, the natural target of HTLV-I.…”
Section: Introductionmentioning
confidence: 99%
“…From the role of PDZ proteins in signal transduction their interactions with Tax might also play a role in the appearance of proliferative disorders. Interestingly, Yamaoka et al have reported that the entire Tax protein fused to the Vp16 activation domain, thereby presenting a di erent C-terminal sequence, loses its ability to transform rat ®broblasts (Yamaoka et al, 1996). The inability to interact with PDZ proteins therefore correlates with the loss of the transforming properties.…”
Section: Interaction Of the Viral Protein Tax With Pdz Proteinsmentioning
confidence: 99%
“…The virus-encoded regulatory protein Tax is critical for HTLV-1 replication and is thought to contribute to ATL development (Yoshida, 1993). Tax has been shown to immortalize T lymphocytes and transform rodent cells (Grassmann et al, 1989;Yamaoka et al, 1996). Transgenic mice that express Tax in mature T lymphocytes developed large granular lymphocytic leukemia, showing that Tax has the capacity to induce leukemia (Grossman et al, 1995).…”
Section: Introductionmentioning
confidence: 99%